Relationship between recognition, training and work-life balance to employee engagaement in CTRM Aerospace Composite Sdn Bhd / Mohd Aliff Asyraf Mahazir - Mahazir, Mohd Aliff Asyraf (Faculty of Business and Management, 2018)
Employee engagement has emerged as a critical organizational issue since businesses are recovering from the trauma of the global recession. Employee engagement has been an area of interest among many researchers and it had received a greater recognition among consulting firms. Therefore, there is a need for academic research on the construct to ascertain the claims of the human resource consulting firms as well as to add to the existing knowledge of employee engagement in the literature.